Columnar Aerosol Extinction Characteristics: Measurements from a Free-Tropospheric Observatory in Western-Himalayas - Gogoi, Mukunda M; Chaubey, Jai Prakash; Sreekanth, V; Kompalli, Sobhan Kumar; Babu, S Suresh; Prabhu, Tushar P; Moorthy, K Krishna (Journal of the Institute of Engineering, 2012)
Continuous measurements of spectral aerosol optical depths (AOD) were made over a very high altitude aerosol observatory at Hanle (32.76°N, 78.95°E, 4520 m amsl), during the summer and autumn of 2009 and 2010, by using a 10-channel multi-wavelength radiometer (MWR). The results depicted very low values of AOD (with a mean for the measurement period as 0.071 ± 0.003 at 500 nm), but with a spectral dependence that changed with the months from 0.8 to 1.3, with a mean value of 1.01 ± 0.06. The AODs though were in general comparable to those seen over pristine Antarctic environments, are quite significant when we consider the altitude of the station. The details are presented. DOI: http://dx.doi.org/10.3126/jie.v8i3.5931 JIE 2011; 8(3): 52-57